PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS NEARPOD PADA MATERI IDE POKOK DI KELAS IV SDN 14 INDRALAYA UTARA - Rinda Amallia Wardani; Fahmi Surya Adikara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a Nearpod-based learning media for teaching main ideas to fourth-grade students at SDN 14 Indralaya Utara. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the media development showed that Nearpod effectively facilitated interactive learning and improved students’ understanding of main idea concepts. Expert validation indicated a high level of validity, and student trials revealed high practicality and improved learning outcomes. Nearpod proved to be an effective and engaging medium to support Indonesian language learning at the elementary level.